Report of two siblings with APECED in Serbia: is there a founder effect of c.769C>T AIRE genotype? - Alessandra Fierabracci; Mariafrancesca Lanzillotta; Ivana Vorgučin; Alessia Palma; Dragan Katanić; Corrado Betterle (BMC, 2021)
Abstract Background Autoimmune polyendocrinopathy-candidiasis-ectodermal-dystrophy (APECED) or autoimmune polyglandular syndrome Type 1 is a rare autosomal recessive syndrome. The disorder is caused by mutations in the AIRE (AutoImmune Regulator) gene. According to the classic criteria, clinical diagnosis requires the presence of at least two of three main components: chronic mucocutaneous candidiasis, hypoparathyroidism and primary adrenal insufficiency. Furthermore, patients are often affected by other endocrine or non-endocrine associated autoimmune conditions. The enrichment of the non-classical triad seems to occur differently in different cohorts. Screenings of the population revealed that homozygous AIRE mutations c.769C > T, c.415C > T and c.254A > G have a founder effect in Finnish, Sardinian and Iranian Jew populations respectively. Case presentation We report here the clinical and genetic characteristics of two new Serbian APECED siblings, one male and one female, actual age of 27 and 24 respectively, born from non-consanguineous parents. Addison's disease was diagnosed in the male at the age of 3.5 and hypoparathyroidism at the age of 4. The female developed hypoparathyroidism at 4 years of age. She presented diffuse alopecia, madarosis, onychomycosis, teeth enamel dysplasia. She further developed Addison's disease at the age of 11 and Hashimoto's thyroiditis at the age of 13.5. She had menarche at the age of 14 but developed autoimmune oophoritis and premature ovarian failure at the age of 16. A treatment with hydrocortisone, fludrocortisone and alfacalcidiol was established for both siblings; L-T4 (levo-thyroxine) for thyroid dysfunction and levonorgestrel and etinilestradiol for POF were also administered to the female. Genetic screening revealed a homozygous c.769C > T (R257X (p.Arg257X)) AIRE mutation. We additionally reviewed the literature on 11 previously published Serbian patients and evaluated the frequency of their main diseases in comparison to Finnish, Sardinian, Turkish, Indian and North/South American cohorts. Conclusion A founder effect was discovered for the R257X genotype detected in the DNA of 10 homozygous and 2 heterozygous patients. Of note, all Serbian APECED patients were affected by adrenal insufficiency and 10 out of 13 patients presented CMC.